Deversifikasi Produk Berbasis Android pada Kelompok Pengrajin Pigura Kaligrafi Kliwon Kabupaten Kudus - Muhammad Arifin; Zuliyati Zuliyati (Universitas Muria Kudus, 2020)
Calligraphy Craftsmen are a part of Micro, Small and Medium Enterprises (MSMEs) that produce various types of Calligraphy Crafts that are highly needed both for interior decoration of houses, offices, prayer rooms, mosques and as souvenirs. The